Sagot :
Answer:
- the correct answer is 1
Step-by-step explanation:
HOPE IT HELPS
PA BRAINLIEST NALANG
Answer:
The answer is 1
Step-by-step Solution:
3(x +2)=5x+4
3x+6=5x+4 ---------------> Distributive Property apply in 3(x+2)
6 = 5x - 3x + 4 ----------> Move the term 3x to right, change sign and simplify
6 = 2x + 4 ------------------> Move 4 to right and change the 4 to -4
6 - 4 = 2x
2 = 2x --------------> Now divide both sides by 2 to cancel 2x coefficient.
2/2 = 2x/2
Final answer: 1
Thank you po pa BRAINLIEST